Gendered roles in Buddhist religious practices in Bhutan: A case study of two nunneries / Sonam Wangmo - Sonam , Wangmo (2017)
There is a general consensus amongst Buddhist scholars that institutional Buddhism, which is the monastic institution is highly patriarchal and have systematically subordinated Buddhist nuns for centuries. Such subordination has resulted in the loss of opportunities for Buddhist nuns to follow the spiritual path laid out by the Buddha, who saw no difference between the spiritual capability of men and women. Loss of opportunities translates into a battle for survival of Buddhist nuns who renounced the comforts of the household life in pursuit of enlightenment. Moreover, elision of nuns from literature on Bhutan has produced a gap in literature, further pushing the nuns into the background. This research fills this gap through an ethnographical study of the religious lives of Vajrayāna Buddhist nuns in two nunneries, one each in Western and Eastern Bhutan. The primary objective of this thesis is to gauge the level of empowerment of nuns in Bhutan, with particular focus on nuns’ access to monastic education and their role in society. The study explored the traditions, practices, scriptures, symbolism and theologies of Vajrayāna Buddhism to determine Bhutanese women's place in the secular and religious realm. The relationship between patriarchal structures in Buddhist institutions and specific Buddhist texts was analysed to understand the root of gender discrimination. This study revealed that the roles of nuns in the two study areas are largely gendered in a manner which denies nuns opportunities for personal development, empowerment and subsequently, opportunities to be able to be more socially engaged. Nuns are still denied access to systematic monastic education, freely available to monks in Bhutan and have issues with basic needs. The results of this study will be used to highlight to the Bhutanese government and monastic institutions in Bhutan the issues surrounding Bhutanese nuns with a view to invoke policy changes on women and religious practice in the country.